Space-Confinement-Induced Synthesis of Pyridinic- and Pyrrolic-Nitrogen-Doped Graphene for the Catalysis of Oxygen Reduction - Ding, Wei; Wei, Zidong; Chen, Siguo; Qi, Xueqiang; Yang, Tao; Hu, Jinsong; Wang, Dong; Wan, Li-Jun; Alvi, Shahnaz Fatima; Li, Li (Angewandte Chemie International Edition, 2013)
Forced obedience: Layer‐structured montmorillonite (MMT) was used as a nanoreactor for the generation of planar pyridinic and pyrrolic N sites in nitrogen‐doped graphene (NG; see picture). The selectivity for the formation of planar N sites was inversely proportional to the interspace width (δ) of the MMT and reached a maximum of 90.27 %. The NG catalyst exhibited low electrical resistance, high electrocatalytic activity, and good stability.